Determining hazard management changes in workplaces following workplace safety inspections by WorkSafeBC in British Columbia, Canada. (August 2021) - Macpherson, Robert A.; Yousefi, Masoud; McLeod, Christopher B.
Highlights: Inspection experience was analysed using a survey of workplace representatives. Over 70% reported inspections led to changes in workplace hazard management. Predictors of changes included officer communication, orders issued, and job role. Inspections can be effective in promoting changes in workplace hazard management. Improved communication is key to improving the inspection experience and impact. Abstract: Workplace safety inspections are an important tool for occupational health and safety agencies to ensure compliance with regulation and promote safer workplaces. While several studies have examined how inspections can improve compliance and reduce workplace injuries, less is known about the role they play in promoting changes in workplace hazard management. The objective of this study is to identify what factors best determine hazard management changes in workplaces following workplace safety inspections in British Columbia, Canada. Using data from the WorkSafeBC Inspection Experience and Impact telephone survey, descriptive statistics and multinomial logistic regression models were used to identify what individual, employer, inspection and survey-related variables best determined hazard management changes following workplace inspections. Among the 1, 578 participants with valid responses, over 70% reported that the inspection led to changes in how hazards were managed at their workplace. Factors that best determined the variability in changes of workplace hazard management included the rating of the officer's ability to explain ways to manage hazards and changes needed to be compliant with regulation, respondents' job role, type of inspection, whether the inspection included orders, and whether or not a post-inspection discussion took place. The findings suggest that workplace inspections can be a useful tool in promoting changes in how hazards are managed at workplaces. Furthermore, the findings highlight areas in which inspections and the inspection experience can be improved, such as targeting key industry sectors and focusing on improved communication between officers and workplace representatives.